Cohésion, cohérence et digression dans le discours à dominante explicative : une perspective diachronique (de la fin du XIIIe au XVIe siècle) - Sabine Lehmann (Discours)
Digression is a type of textual movement that interrupts the flow by disrupting the chronology of the text. The effect of the insertion may be compared to that of parentheses within the textual flow. Digression may be considered similar to the exemplum and the illustration. The similarity lies in the effect of the diversion introduced into the fabric of the text. In this article, we show that digression always indicates a strategy that contributes to the creation of cohesion and coherence effects. It is part of the move towards complexity of the textual and sequential structures observable in the development of French over time. The timeframe established in our study is built around the Middle French period, which is characterized by the appearance of texts that are predominantly explanatory or in support of an argument. The development of these new types of text goes hand in hand with a new concept of discursive coherence. It is in these new types of text representing diverse areas of knowledge (for example medicine, philosophy, agriculture) that we are studying the methods by which the digression is inserted. These methods might be of an implicit or explicit nature (with markers allowing the reader to detect the start and/or end of a digression). The markers used allow the discourse to be punctuated and hence contribute to its stratification.